The Evaluation of Clostridium difficile Toxin A ve B Positivity Rates and Epidemiological Characteristics in Febrile Neutropenic Patients with Diarrhea - Nur EFE İRİS; Aslıhan DEMİREL; Safiye KOÇULU; Esin ÇEVİK; Aylin ORDU; Reyhan DİZ KÜÇÜKKAYA (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: Clostridium difficile (C. difficile) is the most commonly identified causative agent of antibiotic-associated diarrhea. Since immunosuppression is a significant risk factor in febrile neutropenic patients who complain of diarrhea, investigation of toxin A/B is recommended. In this study we aimed at investigating the frequency of C. difficile toxin A or B in stools of patients with malignancies who developed diarrhea during the febrile neutropenic period and to analyze the epidemiological characteristics of toxin-positive patients. Materials and Methods: We analyzed stool samples of patients who were admitted to our hospital. These patients either had hematological malignancies or solid organ tumors and they had developed diarrhea during the febrile neutropenic period. The frequency of C. difficile toxin A and B was identified with chromatographic immunoassay method by using a commercial kit (MonlabTest, Spain) that allowed for qualitative identification of C. difficile toxins A and B at the same time. Results: From January 1, 2012 to August 15, 2015, 197 stool samples were analyzed. C. difficile toxin A+B positivity was identified in 9 samples (4.6%), Ascaris eggs were detected in 14 samples (7%) and Salmonella spp. were found in one sample. The mean age of the toxin-positive patients (6 female, 3 male) was 63.5 years; seven had hematological malignancies (78%) and two had solid organ tumors (22%). All the cases had a history of multiple antibiotic treatments. Seven patients had a history of quinolone prophylaxis, two patients had a history of intensive care admission and all the patients had long-term hospitalization with a mean length of 46 days hospitalization. Conclusion: In febrile neutropenic patients with diarrhea, the rate of C. difficile toxin A+B positivity was 4.6%. Having a history of chemotherapy, quinolone prophylaxis, carbapenem use, long-term hospitalization, and use of multiple antimicrobials were found to be common epidemiological characteristics.